Poetry Slam, ágoras contemporâneas de escrevivências: poética política de jovens artivistas das periferias de São Paulo - Rodrigues, Francisco Cesar (2024)
The proposed study aims to investigate the Slam poetry movement in the city of São Paulo from the perspectives of everyday life in the peripheries, where the paradox of potency and lack coexist and feed into each other. It seeks to research how this experience influences the creative process of peripheral artists through the exercise of narrating their experiences and stories, as conceptualized by Conceição Evaristo as "Escrevivência" (Write-living). Furthermore, it aims to explore the sociopolitical character that contributes to the awakening of a critical and social consciousness, bringing critical and formative thinking to the marginalized areas. To achieve these objectives, the investigative work will be guided by the following aims: explore the recognition of peripheral poetry as a symbolic language of (re)existence and social transformation; investigate the process of elaboration, writing, and recitation of poetry by the poets, based on their daily experiences; analyze Slams as a movement of expression and political participation of peripheral youth who use art as a form of expression and awareness. In order to achieve these objectives, the research process involved fieldwork, interviewing poets Tawane Theodoro and Jéssica Campos, both residents of the Capão Redondo neighborhood in the southern zone of São Paulo, and poet Humberto Marques Messias (Kenyt), a resident of the Ermelino Matarazzo neighborhood in the eastern zone of the capital. A key factor in ensuring an interactive and dynamic research process was the choice to conduct it in movement and circulation within the territories where the poets live and interact, thereby capturing contextualized information and any other relevant aspects that could enrich the approach. Existing records and personal archives were also used to complement the data and information gathered. Ultimately, the aim is to contribute to a deeper understanding of the Slam poetry movement in São Paulo, from its relationship with the environment, to its creation process, and its impact on the lives of poets and the general population. By understanding the experience in the territory, its expression in poetic creation, and the awakening/potentialization of political activism, we can better evaluate the transformative potential of this cultural movement